Land Use Conversion and Soil Properties in a Lowland Tropical Landscape of Papua New Guinea - George, Nangu; Killur, Rajashekhar Rao Bangadi; Cornelio, David Lopez (Jurnal Manajemen Hutan Tropika, 2013)
Land use conversion affects natural soil processes and can potentially decrease soils productivity. A representative area was selected to study the effects of land use conversion in Unitech Campus, Southeastern lowlands of Papua New Guinea (PNG). Area selected for the study was once covered by tropical rainforest and has been subjected to various land use types over time. Representative soil samples were collected under 4 main land use types (secondary forest, plantation forest, grassland, and agricultural garden) at 2 depths (0-0.15 m and 0.15-0.30 m) with 3 replicates per land use. Soil bulk density, water infiltration rate, and cumulative water infiltration values were significantly greater (p < 0.05) under grasslands than under secondary and plantation forests. Among soil chemical properties, extractable potassium content and pH showed significant differences (p < 0.05) among the land uses, pH values increased upon conversion of forested lands to grassland or agricultural gardens. Conversion of secondary forests into grasslands or agricultural gardens leads to depletion of Bray’s phosphorus and extractable potassium. Tree-based land uses were optimum due to better nutrient cycling conditions and lower bulk density compared to grassland and agricultural garden despite the low pH conditions and lower water infiltration.